Fostering science awareness through outreach workshops: bridging the gap between science and society - Harshita Agarwal; Jayesh Dhaiya; Bhumika Pippal; Shaheen Hasan; Neha Jain (Journal of Microbiology & Biology Education)
ABSTRACT Nurturing scientific understanding is the foundation for fostering community-driven solutions to pressing global challenges such as public health. Educating young minds is one of the most effective ways to build resilient, self-sufficient, and sustainable societies ready to confront issues of limited awareness about the microbial world, good hygiene practices, and the growing threat of antimicrobial resistance (AMR), a critical concern in India. This paper details the unique science outreach initiative, led by an all-women team, designed to enhance awareness about the unseen microbial world, their importance in our daily life, good hygiene practices, and the growing threat of AMR. Conducted over 2 years, our team delivered 23 hands-on workshops across five districts in Rajasthan (India), engaging school students and biology undergraduates. Our workshops provided a fascinating window into the invisible world of microorganisms and their role in ecosystems while also driving home the dangers of antibiotic misuse and AMR. In the first series, we offered hands-on experiences that demystified microbes and the necessity of good hygiene practices. The second series of our workshop specifically targeted AMR, with activities to raise awareness about the appropriate use of antibiotics and the consequences of misuse. In addition to promoting scientific awareness, our outreach also emphasized "frugal science," that is, using low-cost, accessible methods to explore complex phenomena. This proved to be a wonderful pedagogical tool, making science approachable for students from diverse backgrounds. Positive feedback from students and the scientific community demonstrates the efficacy of our outreach program, as more than 800 students benefited from our initiative. Our initiative made science more approachable, inspiring students to apply their knowledge to real-world health challenges while fostering scientific curiosity, societal engagement, and empowerment to contribute to the scientific community. Furthermore, our initiative contributes to the groundwork to address global health threats like AMR while serving as a model for taking science to society. We also provide a set of practical tips and tools for educators and outreach practitioners seeking to adapt our approach.